Variaciones de los espectros polínicos de miel y carga corbicular en un colmenar de Santa Rosa, La Pampa (Semiárida, 2020)
In order to study the behavior between the hives in one apiary, the pollen spectra of pollen basket and honey samples were analyzed. The samples were taken at the same lime from five similar hives during 2 months. A total of 30 pollen types were Identified, 5 of them were found exclusively in pollen basket samples, 11 taxa in honey samples and 14 pollen types were common in both. Al both activities the colonies showed high selectivity and the bees preferred a few species called primary source (percentage higher than 10). The taxonomic richness, higher in honey than in pollen basket, was due lo pollution from different airborne pollen grains. The high values of correlation between pollen spectra of corbiculares and honeys, removed all the same lime from different hives, suggest a similar behavior in the explotation of vegetable resource. This uniformity shows that a few colonies may be used to provide a good representation of both activities in the whole apiary.Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.) Presentado en las Jornadas Pampeanas de Ciencias Naturales, 1-3 de diciembre de 1999. Santa Rosa. La Pampa: 253-260.